Development Of CDMA Wireless Sensor Network - Ooi, Teik Chen (Universiti Sains Malaysia, 2018)
Wireless sensor network (WSN) is a technology which had been proposed as an approach to monitor environment condition, health condition, public safety and many other applications. In this project WSN will be used to detect fire at different areas. The problem statement of this project is the issue of limited channel bandwidth of WSN for wider detection area. The objectives of this project are to develop an efficient WSN for fire detection system using the code division multiple access (CDMA) wireless transmission, and to design a WSN which able to collect and to monitor the required data for fire detection. CDMA Walsh code was used to spread the collected data signal over the limited channel bandwidth to differentiate the signal among the nodes. In this project, sensor nodes equipped with temperature sensors and CO gas sensors to collect data from the environment. CSMA/CA MAC protocol was implemented to handle the multiple transmissions from the sensor nodes. A mobile phone app was devised to allow the user to monitor the sensors readings uploaded to IoT platform of the area located with the sensor node. The maximum distance of data transmission is 115 m. The temperature sensor readings and the digital thermometer readings shows average percentage error of 1.08%. The CO gas sensor shows the reading above 10 when burning smoke is detected. A smartphone application had been devised to allow user to monitor the fire parameter for fire prevention. The WSN had been developed successfully with CDMA transmission method and it able to collect and to monitor data for fire detection. In future work, an antenna with higher gain can be used to improve the distance of data transmission. More sensors can increase the accuracy of the fire detection. A special CDMA antenna which able to receive multiple signals simultaneously can be designed to handle the multiple access from more sensor nodes.